(untitled) (Південний архів (історичні науки), 2024)
The purpose is to analyze the materials of the historical and local studies readings «Kryvorizhia: a look into the past…» as a component of the research life of the city, a tool for popularizing local history knowledge and attracting scholars, museum workers, amateur historians, young researchers and all those interested in researching the history of the region. The methodological basis of the research is local history and oral history. Results. Historical and local studies of Kryvyi Rih region have been conducted for more than 80 years. During this time, a group of local historians was formed who studied the history of their native land. They collected and ordered a significant number of sources and literature devoted to local history issues. Since 2015, on the initiative of the Department of History of Ukraine and Law and the Museum of History of the Kryvyi Rih State Pedagogical University (KSPU), the annual historical and local studies readings «Kryvorizhia: a look into the past…» have been launched. Researchers, teachers, students, museum staff, archival workers, amateur local historians, library workers, schoolteachers and high school students, media workers, representatives of public organizations are invited to participate in local history readings. For consideration, participants are offered interesting and relevant topics that highlight various aspects of the history of Kryvyi Rih region in retrospect. During its existence, historical and local studies readings took place in various formats (plenary and sectional meetings, round table, etc.). Under objective circumstances, since 2020, readings have been held in the format of an online conference. Participation in the work of local studies readings provides an opportunity for personal contribution to the historical research of the city, fosters responsibility for the preservation of historical memory and encourages new generations of researchers to study the history of their city. Conclusions. The materials of historical and local studies readings «Kryvorizhia: a look into the past…» have become an integral part of the research life of the region, preserving the memory of the past and helping to understand modern challenges. Local history studies are ongoing, so we hope that this work will be continued.